A Role for Phosphoinositides in Regulating Plant Nuclear Functions - Dieck, Catherine B.; Boss, Wendy F.; Perera, Imara Y. (Frontiers in Plant Science, 2012)
Nuclear localized inositol phospholipids and inositol phosphates are important for regulating many essential processes in animal cells such as DNA replication, recombination, RNA processing, mRNA export and cell cycle progression. An overview of the current literature suggests that a nuclear phosphoinositide pathway occurs in plants as well. Inositol phospholipids, inositol phosphates and enzymes of the PI pathway have been identified in plant nuclei and are implicated in DNA replication, chromatin remodeling, stress responses and hormone signaling. It is anticipated that future research will help shed light on the functional significance of the plant nuclear PI pathway.